2016
DOI: 10.1161/strokeaha.116.013669
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Comparison of 30-Day Potentially Preventable Readmissions After Stroke in Hawaii

Abstract: Background and Purpose Ethnic disparities in readmission after stroke have been inadequately studied. We sought to compare potentially preventable readmissions (PPR) among a multiethnic population in Hawaii. Methods Hospitalization data in Hawaii from 2007-2012 were assessed to compare ethnic differences in 30-day PPR following stroke-related hospitalizations. Multivariable models using logistic regression were performed to assess the impact of ethnicity on 30-day PPR after controlling for age group (<65, ≥6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…It is possible that a large number of these patients did not survive the index admission, given age is a known risk factor for mortality in sICH. Unsurprisingly, greater comorbidity burden increased patients' odds of readmission, a finding that has been reported previously in other stroke subtypes [18,34]. Compared to hospitals in large metropolitan locations, those in smaller cities experienced lower readmission rates, although this finding may have been influenced by lower case severity in the latter.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It is possible that a large number of these patients did not survive the index admission, given age is a known risk factor for mortality in sICH. Unsurprisingly, greater comorbidity burden increased patients' odds of readmission, a finding that has been reported previously in other stroke subtypes [18,34]. Compared to hospitals in large metropolitan locations, those in smaller cities experienced lower readmission rates, although this finding may have been influenced by lower case severity in the latter.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, characterizing the most common causes of readmission could improve surveillance for complications after discharge that would most likely lead to readmission. A national perspective on 30dRAs after sICH in the United States is lacking, with current data primarily limited to relatively small single institution or single state cohorts [2,7,16,18]. Although a prior study has used the NRD to evaluate 30dRAs among patients with ICH, they included all forms of stroke, did not exclude patients with underlying vascular or neoplastic lesions, and did not provide a detailed analysis of clinically relevant patient characteristics that influenced readmission [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…230 Another study found that increasing comorbidity, insurance type, and mental illness were associated with potentially preventable readmissions, which represented 8.4% of all 30-day readmissions after stroke. 231 Some of the factors that we have found to be associated with readmission, such as age and history of atherosclerotic disease, are hard to influence, but other factors like acute complications, hypertension, atrial fibrillation, and possibly functional outcome, are modifiable and can be targeted to improve both early and late readmissions.…”
Section: Risk Factors For Hospital Readmission After Ischemic Stroke mentioning
confidence: 89%
“…241 Such interventions proved useful in a quality improvement project on stroke patients, with a subsequent reduction of 30-day readmission rates from 9% to 3% and a reduction from 16% to 12% in emergency department visits. 243 diabetes mellitus, heart failure, and dehydration, 230,231 whereas others have reviewed the medical records for determination of readmissions that could have been avoided. 152,248 Between 2% and 31% of all unplanned readmission within 30 days have been considered preventable.…”
Section: The Impact Of Hospital Readmissions On Mortalitymentioning
confidence: 99%